An indicator for sulfuric acid–amine nucleation in atmospheric environments. Issue 9 (19th July 2021) - Cai, Runlong; Yan, Chao; Worsnop, Douglas R.; Bianchi, Federico; Kerminen, Veli-Matti; Liu, Yongchun; Wang, Lin; Zheng, Jun; Kulmala, Markku; Jiang, Jingkun
Abstract: New particle formation (NPF) occurs frequently in various atmospheric environments and it is a major source of ultrafine particles. This study proposes an indicator, I, for the occurrence of NPF in the atmosphere based on the mechanism of H2 SO4 –amine nucleation. It characterizes the synergistic effects of the governing factors for H2 SO4 –amine nucleation, including H2 SO4 concentration, amine concentrations, the stability of H2 SO4 –amine clusters, and aerosol surface area concentration. Long-term measurements in urban Beijing were used to validate this indicator. Good consistency was found between this indicator and the occurrence of NPF. NPF was usually observed with I  > 1 for typical conditions in urban Beijing. The derivation and expressions of I also indicate a good positive association between the H2 SO4 dimer concentration and NPF, as also verified by measurements. I was shown to be also applicable in urban Shanghai. Copyright © 2021 American Association for Aerosol Research